Answer:
[tex]\boxed{\dfrac{d^2y}{dx^2} = \dfrac{1-6x}{\sqrt{1-4x}}}[/tex]
Step-by-step explanation:
We are given the first derivative, dy/dx, of a function y in terms of x:
[tex]\dfrac{dy}{dx} = x\sqrt{1-4x}[/tex]
and we are asked to solve for the second derivative:
[tex]\dfrac{d^2y}{dx^2}[/tex]
To do this, we simply have to take the derivative of both sides of the given first derivative:
[tex]\dfrac{d}{dx}\!\left(\dfrac{dy}{dx}\right) = \dfrac{d}{dx}\!\left(x\sqrt{1-4x}\,\right)[/tex]
[tex]\implies \dfrac{d^2y}{dx^2} = \dfrac{d}{dx}\!\left(x\sqrt{1-4x}\,\right)[/tex]
We can differentiate the left side using the product rule, chain rule, and power rule:
- [tex](f\cdot g)' = f\cdot g' - g\cdot f'[/tex]
- [tex]\left[ \dfrac{}{}f(g(x)) \dfrac{}{}\right]' = f'(g(x)) \cdot g'(x)[/tex]
- [tex](x^n)' = nx^{n-1}[/tex]
↓ applying the product rule
[tex]\dfrac{d^2y}{dx^2} = x \cdot \dfrac{d}{dx}\!\left(\sqrt{1-4x}\,\right) + \sqrt{1-4x} \cdot \dfrac{d}{dx}(x)[/tex]
↓ applying the chain and power rules
[tex]= x \left(\dfrac{1}{2}(1-4x)^{\left(\frac{1}2 - 1\right)} \cdot (-4) \right) + \sqrt{1-4x} \cdot 1[/tex]
[tex]= \dfrac{-4x}{2\sqrt{1-4x}} + \sqrt{1-4x}[/tex]
[tex]= \dfrac{-2x}{\sqrt{1-4x}} + \sqrt{1-4x}[/tex]
↓ combining both terms over a common denominator
[tex]= \dfrac{-2x}{\sqrt{1-4x}} + \sqrt{1-4x}\left(\dfrac{\sqrt{1-4x}}{\sqrt{1-4x}}\right)[/tex]
[tex]= \dfrac{-2x}{\sqrt{1-4x}} + \dfrac{1-4x}{\sqrt{1-4x}}[/tex]
[tex]= \dfrac{-2x + (1-4x)}{\sqrt{1-4x}}[/tex]
[tex]\boxed{\dfrac{d^2y}{dx^2} = \dfrac{1-6x}{\sqrt{1-4x}}}[/tex]